2016
DOI: 10.1371/journal.pone.0154369
|View full text |Cite
|
Sign up to set email alerts
|

Association of DPP4 Gene Polymorphisms with Type 2 Diabetes Mellitus in Malaysian Subjects

Abstract: BackgroundGenetic polymorphisms of the Dipeptidyl Peptidase 4 (DPP4) gene may play a role in the etiology of type 2 diabetes mellitus (T2DM). This study aimed to investigate the possible association of single nucleotide polymorphisms (SNPs) of the DPP4 gene in Malaysian subjects with T2DM and evaluated whether they had an effect on the serum levels of soluble dipeptidyl peptidase 4 (sDPP-IV).MethodTen DPP4 SNPs were genotyped by TaqMan genotyping assays in 314 subjects with T2DM and 235 controls. Of these, 71 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 50 publications
0
29
0
Order By: Relevance
“…Mature DPP4 is embedded in the plasma membrane as a homodimer and each monomer consists of an N-terminal cytoplasmic domain, followed by a transmembrane domain and a large ectodomain, which can be further subdivided into a short stalk domain, a glycosylation-rich and a cysteine-rich region as well as the C-terminal catalytic domain (α/ β-hydrolase domain) [26]. Polymorphisms in the DPP4 gene were implicated in several diseases and conditions, including diabetes [27,28] and myocardial infarction [29] but their potential impact on MERS-CoV infection has not been analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Mature DPP4 is embedded in the plasma membrane as a homodimer and each monomer consists of an N-terminal cytoplasmic domain, followed by a transmembrane domain and a large ectodomain, which can be further subdivided into a short stalk domain, a glycosylation-rich and a cysteine-rich region as well as the C-terminal catalytic domain (α/ β-hydrolase domain) [26]. Polymorphisms in the DPP4 gene were implicated in several diseases and conditions, including diabetes [27,28] and myocardial infarction [29] but their potential impact on MERS-CoV infection has not been analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the rs4664446 GG genotype (homozygous wild type) was associated with lower DPP4 antigen levels during placebo. Ahmed et al reported that a different SNP variant, rs4664443 G>A, is associated with both diabetes and increased circulating DPP4 antigen concentrations in Malaysian individuals with T2DM [ 27 ]. They did not report testing for variants of rs4664446.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, DPP4 is an adipokine with increased expression in obesity [10,16], FL [17], and type 2 diabetes mellitus (T2DM) [18] abnormalities that coexist with chronic in ammation. Several single nucleotide polymorphisms (SNPs) have been described in the DPP4 gene (located in region 2q24.3), some of which have been associated with rheumatoid arthritis [19], T2DM, variation in DPP4 [20] and apolipoprotein B (apo B) levels [21], and with increased risk of myocardial infarction in patients with coronary artery disease (CAD) [22]. Considering the high prevalence of obesity and comorbidities such as T2DM [23] and HA in the Mexican population [3] and that the expression of DPP4 is increased in these abnormalities, the aim of the present study was to evaluate the association of the DPP4 polymorphisms with the presence of HA and with DPP4 levels in a cohort of Mexican individuals.…”
Section: Introductionmentioning
confidence: 99%